2017
DOI: 10.1038/srep41456
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199a-5p promotes tumour growth by dual-targeting PIAS3 and p27 in human osteosarcoma

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy and remains a leading cause of cancer-related deaths in adolescents. Emerging evidence indicates that microRNAs (miRNAs) are correlated with clinical and biological characteristics of OS. However, the involvement of miR-199a-5p in OS development remains unclear. In this study, we examined the function of miR-199a-5p in vitro and in vivo. The results showed that miR-199a-5p was significantly up-regulated in OS patient tissues and cells. The inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
(52 reference statements)
0
41
0
1
Order By: Relevance
“…Extensive investigations of the role of miR‐199a‐5p in colorectal cancer showed that the overexpression of miR‐199a‐5p inhibited cell proliferation, migration, invasion, and induced cell apoptosis via targeting the expression of Rho‐associated coiled coil‐containing protein kinase 1 . In osteosarcoma, miR‐199a‐5p was found upregulated in tumor tissues and its downregulation led to cell proliferation and tumor growth inhibition . By introduction the miR‐199a‐5p inhibitor in an osteosarcoma xenograft model, the tumor volume and weight were significantly decreased, indicating the potential to use miR‐199a‐5p as a therapeutic target .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations of the role of miR‐199a‐5p in colorectal cancer showed that the overexpression of miR‐199a‐5p inhibited cell proliferation, migration, invasion, and induced cell apoptosis via targeting the expression of Rho‐associated coiled coil‐containing protein kinase 1 . In osteosarcoma, miR‐199a‐5p was found upregulated in tumor tissues and its downregulation led to cell proliferation and tumor growth inhibition . By introduction the miR‐199a‐5p inhibitor in an osteosarcoma xenograft model, the tumor volume and weight were significantly decreased, indicating the potential to use miR‐199a‐5p as a therapeutic target .…”
Section: Introductionmentioning
confidence: 99%
“…The miR-199a-5p directly binds to the 3′UTRs of the mRNA of both PIAS3 and p27 Kip1 and mediates the reduction of PIAS3 and p27 Kip1 proteins. The miR-199a-5p stimulates the STAT3, cell cycle progression, and tumor growth in osteosarcoma cells 36 . The miR-199a-5p promotes migration and tube formation of human cytomegalovirus-infected endothelial cells through downregulation of SIRT1 and eNOS 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that miRNAs function as oncogenes or tumor suppressors to regulate the expression of cancer-associated genes ( 10 , 11 ). Certain miRNAs have been demonstrated to be involved in OS progression: miRNA-503 suppresses cell proliferation and invasion in OS via targeting insulin-like growth factor 1 receptor ( 12 ); miR-187 inhibits tumor growth and invasion by directly targeting mitogen activated protein kinase 12 in OS ( 13 ); miRNA-199a-5p promotes tumor growth by dually targeting protein inhibitor of activated signal transducer and activator of transcription 3 and cyclin-dependent kinase inhibitor 1B in human OS ( 14 ). In a previous study, performed by Yin et al ( 9 ), miR-491 was identified to be downregulated in OS and to serve as a tumor suppressor, revealing that the upregulation of miRNA-491-5p suppressed proliferation and promoted apoptosis by targeting FOXP4 in human OS.…”
Section: Discussionmentioning
confidence: 99%